The Use Of Natural Pozzolana As An Alternative To Portland Cement With Recycled Pebbles For The Manufacture Of Concrete With Environmental Properties - Wassouf, Moustafa (Latakia University Journal -Engineering Sciences Series, 2025)
The construction industry is considered one of the main causes of environmental degradation due to the use of traditional building materials such as cement. As a result, there appears to be an urgent need to develop sustainable alternatives for producing green concrete using natural, unmanufactured materials. While recognizing the importance of cement in human urbanization, its large use clearly contributes to global warming that threatens the environment globally due to carbon dioxide emissions when fossil fuels are used to melt the products that are used in its manufacture, which are a mixture of clay, water and lime, to produce the main binding material in cement is clinker. This research aims to study the replacement of Portland cement with natural pozzolana according to replacement ratios ranging between 10% and 50%, and to study the effect of this replacement on the physical properties, the most important of which is thermal conductivity, and the mechanical properties represented by resistance to simple pressure, with the use of recycled gravel as an alternative to natural gravel Which in turn helps achieve sustainable development by preserving natural resources. The results showed that by increasing the percentage of replacement of cement with pozzolana, the thermal resistance of concrete increases, since replacing cement with an equal mass of pozzolana leads to a decrease in thermal conductivity by 5%. Also, recycled aggregates show greater thermal resistance compared to natural aggregates, since when replacing 50% of cement with ground pozzolana. We observe an increase in resistance by more than 24%, and a slight decrease in the compression resistance of the resulting concrete is acceptable if the replacement with pozzolana is less than 50%.